“Parno Sar Papin – White as a Swan”, Or How Metaphors Help Roma Children to Acquire Grammatical Categories in Romani - Kyuchukov, Hristo (East European Journal of Psycholinguistics, 2017)
The paper presents the process of language socialization and acquisition of grammatical categories through the Roma oral culture in which metaphors are extensively used. Roma children who grow up in extended Roma families and community learn the language through communication with speakers of different registers. Research with 22 Roma children between three and six years of age from Croatia was carried in order to find out what grammatical categories are learned in this period of the life of children. The children were tested with a specially designed language assessment test in Romani (Kyuchukov & de Villiers, 2014b). The results show that Roma boys perform the test much better than Roma girls. Boys learn Romani from folkloristic genres which are rich in metaphors and this helps them to acquire complex grammatical categories. References Beller, S. (2008). Fostering Language Acquisition in Daycare Settings. The Hague: Bernard van Leer Foundation. Black, B. & Logan, A. (1995). Links between communication patterns in mother-child, father-child, and child-peer interactions and children’s social status. Child Development, 66, 255–271. Bloom, L. et al. (1996). Early conversations and word learning: contributions form child and adult. Child Development, 67, 3154–3175. Blount, B. (1995). Parental speech and language acquisition: and anthropological perspective. In: Language, Culture, and Society. A book of Readings. Second edition, (pp. 551–566). B. Blount (ed.). Prospect Heights, IL: Waveland Press. Bokus, B. & Garstka, T. (2009). Toward a shared metaphoric meaning in children’s discourse. The role of argumentation. Polish Psychological Bulletin, 40(4), 193–203. Bowdle, B. (1998) Alignment and Abstraction in Metaphor. In: Advances in Analogy Research: Integration of Theory and Data form the Cognitive, Computational and Neutral Sciences, (pp. 300–307). K. Holiyok, D. Gentner & K. Kokinov (Eds.). Sofia: New Bulgarian University. Crystal, D. (1992). An Encyclopedic Dictionary of Language and Languages. London: Penguin Dryll, E. (2009). Changes in metaphor comprehension in children. Polish Psychological Bulletin, 40(4), 204 – 212. Elbers, E., Maier, R., Hoekstra, T., Hoogsteder, M. (1992) Internalization and adult-child interaction. Learning and Instruction, 2, 101–118. Ervin, S. & Miller, W. (1972). Language Development. In: Readings in the Sociology of Language, (pp. 68–98). J. Fishman (ed.). The Hague: Mouton. Gleason, J. Berko (1992). Language Acquisition and Socialization. University Lecture. Boston: Boston University Press. Granquist, K. (2012). Metaphors of Finish Roma in Finish and Romani. In: Endangered Metaphors, (pp. 293–313). A. Idstrom, T. Falzett, E. Piirainen (eds.). Amsterdam: John Benjamins Publishing Company. Haslett, B. (1989). Communication and language acquisition within a cultural context. In: Language, Communication and Culture. Current Directions, (pp. 19–34). S. TingToomey & F. Korzenny (eds.). Newbury Park, CA: SAGE Publications. Hoff, E. (2003). Language development in childhood. In: Handbook of Psychology. Vol. 6. Developmental Psychology, (pp. 171– 193). R. Lerner, M.A. Easterbrooks, J. Mistry (eds.). Hoboken, NJ: John Wiley &Sons. Kubanik, P. (2016). Using Romani in language socialization in a Czech family. In: Roma: Past, Present, Future, (pp. 238–249). H. Kyuchukov, E. Marushiakova & V. Popov (eds). Munich: Lincom, Kyuchukov, H. (2014a). Acquisition of Romani in a bilingual context. Psychology of Language and Communication, 18, 211–225. Kyuchukov, H. (2014b). Romani language assessment of Roma children. Journal of Language and Cultural Education, 2, 52–64. Kyuchukov, H. (2010). Romani language competence. In: Situation of Roma Minority in Czech, Hungary, Poland and Slovakia, (pp. 427–465). J. Balvin and L. Kwadrants (eds.). Wroclaw: Prom. Kyuchukov, H. & de Villiers, J. (2014a). Roma children’s knowledge on Romani. Journal of Psycholinguistics, 19, 58–65. Kyuchukov, H. & de Villiers, J. (2014b) Addressing the rights of Roma children for a language assessment in their native language of Romani. Poster presented at the 35th Annual Symposium on Research in Child Language Disorders. Madison, Wisconsin June 12–14. Kyuchukov, H., Kaleja, M. &Samko, M. (2016). Roma parents as educators of their children. Intercultural Education, 26, 444–448. Lakoff, G. & Johnson, M. (1980). Metaphors We Live By. Chicago: The University of Chicago Press. Macwhinney, B. (2001) First language acquisition. In: The Handbook of Linguistics, (pp. 466–489). M. Aronoff & J. Rees-Miller (eds.). Oxford: Blackwell Publisher. Ochs, E. & Schieffelin, B. (1983). Acquiring Conversational Competence. London: Routledge & Kegan Paul. Ochs, E. & Schieffelin, B. (1995). Language acquisition and Socialization: Three developmental stories and their implications. In: Language, Culture, and Society. A book of Readings. Second edition, (pp. 470–512). B. Blount (ed.). Prospect Heights, IL: Waveland Press. Ozcaliskan, S. (2014). Development of metaphor. In: Encyclopedia of language development, (pp. 374–375). P. Brookse, V. Kempe, & G.J. Golson (eds.). NY: Sage Publishers. Penalosa, F. (1981). Introduction to the sociology of language. Rowley, MA: Newbury House Publishers. Rácová, A. & Samko, M. (2015). Structural Patterns and Functions of Reduplicative Constructions in Slovak Romani. Asian and African Studies, 24, 165–189. Reger, Z. & Gleason, J. Berko (1991). Romani child-directed speech and children’s language among Gypsies in Hungary. Language in Society, 20(4), 601–617. Reger, Z. (1999). Teasing in the linguistic socialization of Gypsy children in Hungary. Acta Linguistica Hungarica, 46(3–4), 289–315. Rondal, J. (1985). Adult-Child Interaction and the Process of Language Acquisition. New York: Praeger Publishers. Samko, M. & Kapalková, S. (2014). Analýza naratívnej schopnosti rómskeho dieťaťa v rómčine a slovenčine. Psychológia a Patopsychológia Dieťaťa, 48, 372–384. Winner, E. (1988). The Point of Words. Children’s Understanding of Metaphor and Irony. Cambridge, MA: Harvard University Press.